A Systems Level Characterization of the Saccharomyces Cerevisiae NuA4 Lysine Acetyltransferase - Mitchell, Leslie (Université d'Ottawa / University of Ottawa, 2011)
Lysine acetylation is a post-translational modification (PTM) studied extensively in the context of histone proteins as a regulator of chromatin dynamics. Recent proteomic studies have revealed that as much as 10% of prokaryotic and mammalian proteins undergo lysine acetylation, and as such, the study of its biological consequences is rapidly expanding to include virtually all cellular processes. Unravelling the complex regulatory network governed by lysine acetylation will require an in depth knowledge of the lysine acetyltransferase enzymes that mediate catalysis, and moreover the development of methods that can identify enzyme-substrate relationships in vivo. This is complex task and will be aided significantly through the use of model organisms and systems biology approaches. The work presented in this thesis explores the function of the highly conserved NuA4 lysine acetyltransferase enzyme complex in the model organism Saccharomyces cerevisiae using systems biology approaches. By exploiting genetic screening tools available to the budding yeast model, I have systematically assessed the cellular roles of NuA4, thereby identifying novel cellular processes impacted by the function of the complex, such as vesicle-mediated transport and the stress response, and moreover identified specific pathways and proteins that are impacted by NuA4 KAT activity, including cytokinesis through the regulation of septin protein dynamics. Moreover, I have developed a mass spectrometry-based technique to identify NuA4-dependent acetylation sites amongst proteins that physically interact with NuA4 in vivo. Together this work demonstrates the diversity of processes impacted by NuA4 function in vivo and moreover highlights the utility of global screening techniques to characterize KAT function.
Keywords: lysine acetylation; functional genomics; NuA4; proteomics